Associations between Pleurisy and the Main Bacterial Pathogens of the Porcine Respiratory Diseases Complex (PRDC) - Petri, Fernando Antônio Moreira [UNESP]; Ferreira, Geovana Coelho [UNESP]; Arruda, Laíza Pinto [UNESP]; Malcher, Clarisse Sena [UNESP]; Storino, Gabriel Yuri [UNESP]; Almeida, Henrique Meiroz de Souza [UNESP]; Sonalio, Karina [UNESP]; Silva, Daniela Gomes da [UNESP]; Oliveira, Luís Guilherme de [UNESP] (MDPI, 2023)
Porcine Respiratory Diseases Complex (PRDC) is a multifactorial disease that involves several bacterial pathogens, including Mycoplasma hyopneumoniae (M. hyopneumoniae), Actinobacillus pleuropneumoniae (A. pleuropneumoniae), Pasteurella multocida (P. multocida), Glaesserella parasuis (G. parasuis), and Streptococcus suis (S. suis). In pigs, the infection may cause lesions such pleurisy, which can lead to carcass condemnation. Hence, 1015 carcasses were selected from three different commercial pig farms, where the respiratory conditions were evaluated using slaughterhouse pleurisy evaluation system (SPES) and classified into five groups. In total, 106 pleural and lung fragments were collected for qPCR testing to identify the five abovementioned pathogens. A moderate correlation between the severity of the lesions and the presence of P. multocida (R = 0.38) and A. pleuropneumoniae (R = 0.28) was observed. Concerning the lung samples, the severity of the lesions was moderately correlated with the presence of P. multocida (R = 0.43) and M. hyopneumoniae (R = 0.35). Moreover, there was a strong correlation between the presence of P. multocida and M.hyopneumoniae in the pleura (R = 0.82). Finally, this approach may be a useful tool to identify and quantify causative agents of PRDC using qPCR, providing a comprehensive evaluation of its relevance, strength, and potential application in the field as a surveillance tool for veterinarians.
Keywords: pig production; slaughterhouse; SPES